Vibration analysis of Kenyir Dam power station structure using a real scale 3D model - Arbain, Azizi; Ahmad Mazlan, Ahmad Zhafran; Zawawi, Mohd Hafiz; Mohd Radzi, Mohd Rashid (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper, the vibration analysis in terms of modal and harmonic responses are investigated for the power station structure of Kenyir Dam in Terengganu, Malaysia. Modal analysis is carried out to provide the dynamic characteristics of the power station which includes the natural frequencies and mode shapes.
Keywords: Kenyir Dam power; vibration analysis; dam structures; using 3D model; Frequency Response Function; Finite Element Method (FEM); moc Kenyir Dam; analiza drgań; konstrukcja zapory; model 3D; FRF; MES